Do investors value block holder diversity? Evidence from an emerging market - Ai-Yee Ooi; Kian-Ping Lim (Chapman & Hall, 2025)
This study examines the relationship between block holder diversity and firm value in Malaysia, an emerging market characterized by principal-principal conflicts. In contrast to recent evidence from the United States documenting negative effects, the analysis hypothesizes that block holder diversity is positively associated with firm value in emerging markets where block holders with divergent interests may be less likely to collude for private benefit extraction. Using a comprehensive dataset of Malaysian publicly listed firms from 2002 to 2019, three distinct measures of block holder diversity are constructed. The baseline analysis and a series of robustness checks reveal a robust positive relationship between block holder diversity and Tobin’s Q. These contrasting findings between developed and emerging markets highlight how the relationship between diverse block holder structures and firm value varies with institutional environment.